The effectiveness of aoksigame cards in improving knowledge, attitudes, and practices of anemia among adolescent girls - Hilda Novita; Tri Siswati; Lastmi Wayansari; Waryana Waryana (DAPU Aceh Publishing, 2025)
Anemia remains a public health problem among adolescent girls in Indonesia. A 2023 national survey reported that 15.5% of adolescents aged 15–24 years experience anemia. Knowledge and compliance with iron supplementation remain low, while conventional education methods are often perceived as less engaging by adolescents. This study aimed to evaluate the effectiveness of Aoksigame Card on improving adolescents’ knowledge, attitudes, and practices in preventing anemia. A quasi-experimental study with a pretest-posttest control group design was conducted on 62 tenth-grade female students from two high schools in Yogyakarta, selected using simple random sampling. The intervention group received education using the Aoksigame Card, while the control group received PowerPoint slide education. Data on knowledge, attitudes, and practices were collected before and after the intervention using a validated and reliable questionnaire. Data were analyzed using SPSS with a significance level of p<0.05. The intervention group showed a significant improvement in knowledge (p=0.003), but not in attitudes (p=0.276) or practices (p=0.083). Intergroup comparison showed a significant difference in knowledge (p=0.017), but not in attitudes (p=0.956) or practices (p=0.232). Aoksigame Card is effective in increasing adolescents’ knowledge of anemia.